Trouble Grist anthology of protest - short stories - Bastow, Caitlin; Crew, Liam; Croft, Jonathan; Crump, Simon; Edwards, Lottie; Greenhalgh, Beth; Rhodes, Charlotte; Ridley-Duff, Beth; Turner-Beach, Georgia (University of Huddersfield Press, 2019)
The latest Grist Anthology is an innovative blend of some of the most exciting and freshest voices in prose today. Protest is the distillation of a simple human experience - to witness a wrong being done, and to do something about it. The stories featured in Trouble celebrate protest, rebellion, disobedience and general bloody-mindedness in all of its forms. The best writing about protest should inspire, educate, motivate, compel and of course, entertain. And that's what this collection is all about. There are historical protest stories here - The Flag, Happy Harpies - stories set in the future - Money Bank, Last of Them - stories of personal protest against sexual and racial discrimination - Meet Me, The Walk of Blood - and the closing story, The Calling, which embodies the simple truth that sometimes all you can do in protest is to make a lot of noise.